2019
DOI: 10.3390/ma12223706
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Arsenic–Doped ZnTe Thin Films as a Back Contact for CdTe Solar Cells

Abstract: As-doped polycrystalline ZnTe layers grown by metalorganic chemical vapor deposition (MOCVD) have been investigated as a back contact for CdTe solar cells. While undoped ZnTe films were essentially insulating, the doped layers showed significant rise in conductivity with increasing As concentration. High p-type carrier densities up 4.5 × 1018 cm−3 was measured by the Hall-effect in heavily doped ZnTe:As films, displaying electrical properties comparable to epitaxial ZnTe single crystalline thin films in the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…216 Arsenic-doped ZnTe layers demonstrated higher conductivity compared to the undoped ZnTe, where on applying a heavily doped p-type 100 nm ZnTe:As back contact with the device architecture of glass/ITO/Cd 1Àx Zn x S/CdTe-CdCl 2 /ZnTe:As/CdS/ CdCl 2 /Au and annealed stack up to ZnTe:As at 420 1C in a hydrogen atmosphere, a significantly enhanced V oc and PCE 11.9% were achieved. 217 To reduce the back contact barrier, ZnTe:Cu was applied with the device architecture of glass/FTO/ SnO 2 /n-CdS/p-CdTe/ZnTe:Cu/Au, and it was revealed that the reaction at the CdTe/ZnTe:Cu interface during the heat treatment process could modify the interfacial band alignment, which reduced the defect-associated recombination and supported the transport of holes, resulting in a PCE of 15.8%. 218 The deposition time and temperature to the ZnTe back contact alter the performance, and accordingly a device was developed with the configuration of glass/FTO/CdS/CdTe/ZnTe/Cu/Au, as depicted in Fig.…”
Section: View Article Onlinementioning
confidence: 99%
“…216 Arsenic-doped ZnTe layers demonstrated higher conductivity compared to the undoped ZnTe, where on applying a heavily doped p-type 100 nm ZnTe:As back contact with the device architecture of glass/ITO/Cd 1Àx Zn x S/CdTe-CdCl 2 /ZnTe:As/CdS/ CdCl 2 /Au and annealed stack up to ZnTe:As at 420 1C in a hydrogen atmosphere, a significantly enhanced V oc and PCE 11.9% were achieved. 217 To reduce the back contact barrier, ZnTe:Cu was applied with the device architecture of glass/FTO/ SnO 2 /n-CdS/p-CdTe/ZnTe:Cu/Au, and it was revealed that the reaction at the CdTe/ZnTe:Cu interface during the heat treatment process could modify the interfacial band alignment, which reduced the defect-associated recombination and supported the transport of holes, resulting in a PCE of 15.8%. 218 The deposition time and temperature to the ZnTe back contact alter the performance, and accordingly a device was developed with the configuration of glass/FTO/CdS/CdTe/ZnTe/Cu/Au, as depicted in Fig.…”
Section: View Article Onlinementioning
confidence: 99%
“…The high bandgap means that ZnTe is not suitable for use as a single absorber in a high PCE solar cell. ZnTe can be doped p-type by pnictides (N, 69 P, 70 As, 71 Sb, 72 and Bi) and by copper. The electron affinity of ZnTe is such that the valence band offset to CdTe is very low.…”
Section: Zinc Telluridementioning
confidence: 99%
“…It is clear from Table 3 that in order to obtain high PCE either the back contact process must contain Cu or the CdTe is already heavily p-type doped (Oklobia et al (2019) 71 used arsenic doping).…”
Section: Zinc Telluridementioning
confidence: 99%
“…It is a p-type semiconductor with a direct bandgap energy of 2.21 to 2.26 eV at room temperature with a low electron affinity of 3.53 eV. [13] Different methods of deposition have been employed by different researchers to synthesize ZnTe thin films: metal-organic chemical vapour deposition (MOCVD) [14], spray pyrolysis [15], electrodeposition [16], thermal [17]. Due to the peculiarity of the thermal evaporation technique capable of forming multiple layers on a single substrate, making it easy to monitor the deposition rate and thickness of the film with a quartz crystal thickness monitor equipped with a vacuum coating unit, there was no wastage of materials and the time-saving technique was necessitated for this study.…”
Section: Introductionmentioning
confidence: 99%
“…An investigation into the structural and optical properties of nanocolumnar ZnTe thin films grown using the glancing angle technique was conducted [12] and determined that the band gap energy of the samples was modified at higher deposition angles, which is promising to be applicable in optoelectronic devices. Also, the properties of arsenic-doped ZnTe thin films as a back contact for CdTe solar cells were studied by [14],…”
Section: Introductionmentioning
confidence: 99%